Binational cohort study comparing the management and outcomes of pregnancy women with a BMI greater than 50-59.9kg/m2 and those with a BMI 60kg/m2 or greater - McCall, S; Li, Z; Kurinczuk, J; Sullivan, E; Knight, M (BMJ Publishing Group, 2018)
Objectives To compare the management, maternal and perinatal outcomes of women with a body mass index (BMI) ≥60 kg/m2 with women with a BMI >50–59.9 kg/m2. Design International collaborative cohort study. Setting Binational study in the UK and Australia. Participants UK: all pregnant women, and Australia: women who gave birth (birth weight ≥400 g or gestation ≥20 weeks) Methods Data from the Australasian Maternity Outcomes Surveillance System and UK Obstetric Surveillance System. Management, maternal and infant outcomes were compared between women with a BMI ≥60 kg/m2 and women with a BMI >50–59.9 kg/m2, using unconditional logistic regression. Results The sociodemographic characteristics and previous medical histories were similar between the 111 women with a BMI ≥60 kg/m2 and the 821 women with a BMI >50–59.9 kg/m2. Women with a BMI ≥60 kg/m2 had higher odds of thromboprophylaxis usage in both the antenatal (24% vs. 12%; OR 2.25, 95% CI 1.39 to 3.64) and postpartum periods (78% vs. 66%; OR 1.68, 95% CI 1.04 to 2.70). Women with BMI ≥60 kg/m2 had nearly double the odds of pre-eclampsia/eclampsia (adjusted OR 1.83 (95% CI 1.01 to 3.30)). No other maternal or perinatal outcomes were statistically significantly different. Severe adverse outcomes such as perinatal death were uncommon in both groups thus limiting the power of these comparisons. The rate of perinatal deaths was 18 per 1000 births for those with BMI ≥60 kg/m2; 12 per 1000 births for those with BMI >50–59.9 kg/m2; those with BMI ≥60 kg/m2 had a non-significant increased odds of perinatal death (unadjusted OR 1.46, 95% CI 0.31 to 6.74). Conclusions Women are managed differently on the basis of BMI even at this extreme as shown by thromboprophylaxis. The pre-eclampsia result suggests that future research should examine whether weight reduction of any amount prior to pregnancy could reduce poor outcomes even if women remain extremely obese.